Prevalence of breast fibroadenoma in healthy physical examination population in Guangdong province of China: a cross-sectional study - Yingjia Li; Lijun Zhu; Xiaoqi Zeng; Shanshan Jiang; Simin Ruan; Huanrong Ma; Changsheng Ye; Jianyu Dong (BMJ Open)
Objective To provide an accurate assessment of the prevalence of breast fibroadenoma in a large population and to confirm the diagnostic accuracy of ultrasound for fibroadenoma.Design This was a cross-sectional survey.Setting This research was conducted at Nanfang Hospital, Guangzhou, Guangdong, China.Participants A total of 11 898 women aged 18–40 years who underwent breast screening between 1 January 2019 and 31 December 2019 were included in the fibroadenoma prevalence study. From 1 June 2019 to 31 December 2019, 342 breast lesions with pathology reports and preoperative ultrasound images were collected for diagnostic fibroadenoma testing (vs histological diagnostic testing).Primary outcome measures Pearson’s χ2 test was performed to compare the prevalence of different lesions between age groups, and descriptive statistics were used to report the clinical characteristics of fibroadenoma. For ultrasound diagnosis, fibroadenoma was defined as a well-circumscribed lesion with round or oval shape, consisting of a homogeneously hypoechoic or isoechoic solid mass, located parallel to the chest wall with a smooth margin and no posterior shadowing. Diagnostic test results for breast fibroadenoma were stratified by diagnostic type (histological vs ultrasound).Results Of the women aged 18–40 years, 27.6% (3285/11 898) had an ultrasound diagnosis offibroadenoma. Of these, the prevalence of fibroadenoma was stable across age groups (p=0.14) and did not differ between the left and right sides of the breast. Almost two-thirds of women presented with a single fibroadenoma, and most fibroadenomas did not exceed 1 cm in size. The sensitivity and specificity for fibroadenoma were 97.0% (95% CI for sensitivity: 93.7% to 98.8%) and 91.4% (95% CI for specificity: 85.4% to 95.5%) for ultrasonography, respectively.Conclusions The prevalence of fibroadenoma in South China is as high as 27.6%, and ultrasound could be used as a tool to diagnose fibroadenoma.